Dzieciństwo, dziecko i jego dobro w perspektywie Korczakowskiej - Małgorzata Turczyk; Justyna Kusztal (Problemy Wczesnej Edukacji)
This article is an attempt to specify the meanings of a child’s category, childhood and the best interest of the child made on the basis of analysis and interpretation of pedagogical thought of Janusz Korczak and literature analysis. The interpretations and references to Korczak’s thoughts have been there included. The research project were based on document content analysis. Korczak – the figure undoubtedly the foreground in Polish pedagogy and the world doctrine of children’s rights. It is his pedagogical practice and contemporary reception of his thoughts, made by educators and lawyers, that will become the basis for seeking the meanings of categories on which the modern doctrine of children’s rights and the system of their protection are built. As a result: the principle of the best interest of the child as a determinant of the pedagogical practice of Janusz Korczak has been normalized in the Convention on the Rights of the Child and other acts of Polish and international law. This category is interpreted dynamically in the context of changes in the discourses of a child and childhood functioning in social and political life, especially in the area of education and upbringing of the young generation. As a pedagogical category, it is visible in the reflection of many pedagogues as a central category, most often identified with the goal of all adult activities for the child.